Biosynthesis of polyhydroxyalkanoate bioplastic from glycerol by engineered Escherichia coli - Chitwadee Phithakrotchanakoon (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
Polyhydroxyalkanoates (PHAs) are potentially used as bio-plastics. However, the high cost of PHAs limits their use in the commodity market. Crude glycerol is an alternative carbon source for PHAs production. Engineered Escherichia coli strains were constructed to investigate their ability to synthesize poly(3-hydroxybutyrate) [P(3HB)] and Short-Chain-Length-co-Medium-Chain-Length PHAs (SCL-MCL-PHAs) from pure and crude glycerol. PHA biosynthesis-related genes: ß-ketothiolase (phaA), acetoacetyl-CoA reductase (phaB) and PHA synthase (phaC), were cloned into pETDuet-ABCs and co-expressed in E. coli for P(3HB) biosynthesis. The phaA and phaB genes were derived from Ralstonia eutropha whereas 3 different phaCs from 3 different bacteria (Aeromonas hydrophila, R. eutropha and Pseudomonas putida) were used. The results showed that the amount of P(3HB) is affected by the type of PhaCs (30 wt%, 24 wt%, and 2 wt% of cell dry weight (CDW), respectively). The stage of cell and the carbon: nitrogen ratio were also found to be the key parameters influencing the amount of P(3HB). To produce SCL-MCL-PHAs, three (R)-specific enoyl-CoA hydratase genes from P. putida (phaJ1[subscript]Pp and phaJ4[subscript]Pp) and from A. hydrophila (phaJ[subscript]Ah) were cloned into pCDFDuet-Js and co-transformed with pETDuet-ABCs. Co-expression of PhaAB with each of PhaCs and PhaJs caused E. coli to produce SCL-MCL-PHAs with different monomer compositions, varying from C4 to C10 from pure glycerol supplemented with dodecanoate. The fractions of MCL-unit were in correlation with the concentration of dodecanoate. When 1% crude glycerol was used as a carbon source, E. coli-ABCAh produced P(3HB) at 14 wt% of CDW; whereas E. coli-ABCAhJAh produced P(3HB-1 mol% 3HHx) at 3 wt% of CDW when dodecanoate was included in the culture media. The molecular weight of PHAs produced was in the range of 110 to 260 kDa and the thermal properties of P(3HB-co-3HHx) were superior to P(3HB).